Optically Induced Cell Fusion Using Bispecific Nanoparticles. Issue 22 (21st June 2013) - Yeheskely‐Hayon, Daniella; Minai, Limor; Golan, Lior; Dann, Eldad J.; Yelin, Dvir
Abstract Redirecting the immune system to eliminate tumor cells is a promising alternative to traditional cancer therapies, most often requiring direct interaction between an immune system effector cell and its target. Herein, a novel approach for selective attachment of malignant cells to antigen‐presenting cells by using bispecific nanoparticles is presented. The engaged cell pairs are then irradiated by a sequence of resonant femtosecond pulses, which results in widespread cell fusion and the consequent formation of hybrid cells. The dual role of gold nanoparticles as conjugating agents and fusion promoters offers a simple yet effective means for specific fusion between different cells. This technology could be useful for a variety of in vitro and in vivo applications that call for selective fusion between cells within a large heterogenic cell population.